Chapter Introduction Transitional Justice in Aparadigmatic Contexts - Destrooper, Tine (Taylor & Francis, 2023)
Introduction: This introduction provides the rationale and theoretical anchoring for the volume and its focus on aparadigmatic cases. It argues that practice and scholarship in paradigmatic transitional justice contexts built a field that conceptualises the state as a partner in the transition. However, due to the field's expansion to aparadigmatic justice contexts, this assumption and its associated binary concepts cannot inform analysis. Instead, as demonstrated by the present volume, transitional justice in aparadigmatic contexts offer different intentions, responses, and experiences of transitional justice. Where the state is not a partner, it may ignore, refuse, resist, and fight, while giving way to other actors and justice articulations. The chapter first conceptualizes transitional justice as the potential for recognition, accountability and disruption. The chapter then discusses the expansion and recent standardisation of the field, whereby transitional justice has become four specific types of mechanisms: trials, truth telling, reparation and institutional reform. Thereafter it analyses the problem of the state, particularly how the field has assumed a transitional state, a partnering state. In the next section it offers a typology of transitional justice contexts that cover both paradigmatic and aparadigmatic contexts and ranges from contexts of ongoing conflict to consolidated democracy in formerly imperial states. This range covers seven different types of transitional justice context organized on the basis of the status of its political authority. Lastly, it maps the volume's chapters onto the typology and briefly introduces each of them.